Hormonal and haematological responses of Clarias gariepinus (Burchell 1822) to nitrite toxicity (2007)
Study on hormonal and haematological responses of Clarias gariepinus to nitrite toxicity was carried out to know the magnitude of the effects of this stressor on fish physiology. Haematological responses of C. gariepinus to sub-lethal levels of nitrite (0.1 g L-1) at different exposure h (0, 6, 24, 48, 72 and 96 h) were carried out. Blood samples of C. gariepinus were collected at each exposure h and evaluated for primary and secondary stress indicators. Data obtained were subjected to simple descriptive analysis, analysis of variance and Pearson Product Moment correlation analysis. When exposed to nitrite, there was progressive increase in plasma cortisol level of C. gariepinus from 0 h (101.00± 0.10 ng dL-1) to 48 h (161.00± 1.20 ng dL-1), this later decreased at 72 h (107.00±1.60 ng dL-1), it increased in 96 h to 136.00±1.00 ng dL-1. PCV and Hb were elevated after 6 h of exposure and decreased significantly (p<0.05) at 48, 72 and 96 h of exposure in fish exposed to sub-lethal level of nitrite. From the value of 3.69±0.01 106/l recorded at 0 h, RBC level decreased significantly (p<0.05) at 6 h, this was followed by significant increase (p<0.05) at 24 h. The RBC value later decreased gradually to 2.20±0.56 106 L-1 at 96 h. The study shows that hormonal and haematology balances of C. gariepinus was affected on short term exposure to nitrite toxicity.